Perancangan Sistem Informasi Berbasis Website Menggunakan Metode Waterfall (Studi Kasus Karang Taruna Unit RW 012) - Danu Bramantio; Abi Sarwan Alwafi; Akmal Bagus Satrio; Saprudin (CV. Multi Kreasi Media, 2025)
The advancement of information technology has driven digital transformation across various sectors, including the dissemination of information. Digital platforms such as websites have become effective tools for delivering information widely and efficiently. Karang Taruna Unit RW 012, as a youth organization, still faces challenges in effectively distributing information about its activities and documentation. This study aims to develop a web-based information system using the Waterfall development model, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The resulting website has proven to expand the reach of information, enhance both internal and external communication, and strengthen the organization’s image in the digital era.